2019
DOI: 10.5812/ijcm.96069
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Hope Assessment in Women with Breast Cancer After Poetry Therapy as a Psychotherapy Method: A 6-Month Follow-Up Study

Abstract: Background: Quality of life in patients with cancer is an important issue. It affects different aspects of the patients' life. Supportive group therapy helps the majority of women with breast cancer to treat their disease and decrease the recurrence of the disease. Group poetry therapy, as a safe method, can be used to increase the quality of life of patients. Objectives: We designed this study to evaluate the effect of poetry therapy on the quality of life of patients with cancer. Methods: A total of 91 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…According to our review, the first article that psychologically investigated Rumi's thoughts was published in 1999 (25). Furthermore, we found that the number of studies has been growing increasingly in recent years, with 10 of 24 studies published in 2020 and 2021 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Also, in recent years, the articles have studied more diverse topics and have been more experimental.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…According to our review, the first article that psychologically investigated Rumi's thoughts was published in 1999 (25). Furthermore, we found that the number of studies has been growing increasingly in recent years, with 10 of 24 studies published in 2020 and 2021 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Also, in recent years, the articles have studied more diverse topics and have been more experimental.…”
Section: Resultsmentioning
confidence: 92%
“…Also, in recent years, the articles have studied more diverse topics and have been more experimental. Since most of the studies were conducted in Iran, only 21% of the studies were written in the English language (21,25,27,32,36). Among the reviewed studies, Rumi's metaphors and allegories have been employed more in cognitive approach (31,32,(36)(37)(38)(39)(40), mindfulness-based approach (21,26,28,29,33,41,42), and existential-humanistic approach (29%, 29%, and 25%, respectively) (25,35,(43)(44)(45)(46).…”
Section: Resultsmentioning
confidence: 99%